2010
DOI: 10.1002/iroh.201011213
|View full text |Cite
|
Sign up to set email alerts
|

Increased Temperature Due to Global Warming Alters the Respiratory Potential in Aquatic Organisms from an Oligotrophic Lake

Abstract: The influence of elevated temperature was studied on the respiratory potential of a microplankton community, two macrophytes species (Myriophyllum spicatum and Chara aspera), and sediments, all from an oligotrophic lake, in order to estimate their susceptibility to temperature change. Samples collected in winter, spring, summer and autumn were incubated at three different temperatures. The respiratory potential, measured as electron transport system (ETS) activity at a standard temperature of 20 °C was, in ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…The increase of respiratory potential in sediments in summer time was therefore probably caused by the higher microbial production rate. The positive correlation between ETS activity of sediment and temperature (r = 0.41, p <0.05) is in accord with the results of the laboratory study that showed that a relatively small increase in temperature induced significantly higher respiratory potential in sediments (Simčič & Germ 2010). Törnblom & Pettersson (1998) also evidenced that temperature was the main factor controlling seasonal changes in bacterial and total sediment metabolism.…”
Section: Respiratory Activity Of Sedimentssupporting
confidence: 87%
See 1 more Smart Citation
“…The increase of respiratory potential in sediments in summer time was therefore probably caused by the higher microbial production rate. The positive correlation between ETS activity of sediment and temperature (r = 0.41, p <0.05) is in accord with the results of the laboratory study that showed that a relatively small increase in temperature induced significantly higher respiratory potential in sediments (Simčič & Germ 2010). Törnblom & Pettersson (1998) also evidenced that temperature was the main factor controlling seasonal changes in bacterial and total sediment metabolism.…”
Section: Respiratory Activity Of Sedimentssupporting
confidence: 87%
“…However we decided to measure respiratory activity of both components that is less time consuming and gives good results (Simčič & Germ 2010). When organisms are exposed to stress and demand more energy, ATP production and O 2 consumption are increased in the mitochondria (Packard 1985;Bartoli et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The reason is probably the use of modified ETS‐assay in this study, where cell‐free supernatant with faster reaction rates was used in contrast to intact soils and sediments in the latter (G.‐Tóth et al ., ). Moreover, the acute response of soils and sediments to temperature was measured here, while Trevors () incubated sediments for 24 h. In contrast, Simčič and Germ () demonstrated a similar increase (up to 64%) in ETSA of lake sediments when incubated at different temperatures (2–24°C), which is comparable with this study (up to 66%).…”
Section: Discussionsupporting
confidence: 84%
“…The stimulation of sexual reproduction by decreasing water levels is thought to be due to increased light availability (Bonis & Grillas 2002, Wang et al 2008. However, possible effects of temperature on the occurrence of gametangia cannot be ignored (Guerlesquin 1990, Simčič & Germ 2010, and temperature might be a more important determinant that light intensity for the maturation of oospores (H. Wang et al unpul. data).…”
Section: Vegetative and Sexual Reproductionmentioning
confidence: 99%